A successful separation of omphalopagus twins during COVID-19 pandemic: A case report - Monica Bellynda; Muhammad David Perdana Putra; Suwardi Suwardi; Nunik Agustriani; Faizal Muhammad (Jurnal Keperawatan Padjadjaran, 2023)
Background: Omphalopagus is a rare condition involving digestive system and abdominal wall fusion. This study reports an omphalopagus case during the early phase of the coronavirus disease 2019 (COVID-19) pandemic in Indonesia.Case: Male conjoined twins, aged 14 months, were diagnosed with omphalopagus and several organ failures. We performed separation surgery of the omphalopagus with primary closure and post-surgical care for fifteen days. The early surgery was preferable in this case due to life-threatening issues of COVID-19, despite omphalopagus separation may cause post-surgical complications. Furthermore, the emerging pandemic conditions also required a more stringent procedure to avoid the risk of viral spread.Conclusion: We conclude that, in the lack of evidence-based instruction for hospital care during the early phase of COVID-19 in Indonesia, life-saving surgical considerations from death due to complications of COVID-19 infection and acute respiratory distress syndrome must be performed and prioritized. However, potential omphalopagus complications must be evaluated.